MANDIU PASILI IN THE TRADITIONAL WEDDING PROCESSIONS OF THE KAILI TRIBE IN PEVUNU VILLAGE, SIGI REGENCY: SEMIOTIC STUDIES (MANDIU PASILI DALAM PROSESI PERNIKAHAN ADAT SUKU KAILI DI DESA PEVUNU KABUPATEN SIGI: KAJIAN SEMIOTIKA) - Efendi Efendi; Ali Ali; Syamsuddin Syamsuddin; Gusti Ketut Alit Suputra; Anjar Kusuma Dewi; Magfirah Nurul Amalia (Universitas PGRI Sumatera Barat, 2023)
Mandiu Pasili is a part of the traditional ceremony that follows the wedding. Mandiu Pasili (Bathing together in front of the door) is a tradition carried out the morning after the wedding at the bride's residence. The research question is,